(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
In the present situation, medication is very difficult. For elderly people, due to their health conditions, it is a very challenging task. In case of wrong medication, it affects the people’s health seriously. Many of the people, from young ones to elders, are forgetting to take the medicine on time. So that to remind the aged people and patients to use the drugs on time only. In this paper, describe a smart medicine box. This is a programmable medicine box, and it gives the remainder to the nurses, elderly people, or patients. This medicine box will issue the remainder in the form of alarm sounds and messages. This system is not only for old people but also for different people who are suffering from various diseases. The major benefit of this proposed system is saving the drug details and taking it on time. This system sends the alert message to the user when the box is going to be empty. The smart medicine system is very useful for patients having long-term medical problems. This proposal contains various important features, like giving the alert message to the patient through the phone application, the correct time to take the drug, the dosage of the drug, and the remaining number of drugs available in the box.